Case Report: Two Cases of Abdominal Aggressive Fibromatosis That Mimicked Abdominal Wall Endometriosis and Review of Literature - Chen, Xin; Wang, Yuan; Liu, Haiyuan; Shi, Honghui; Fan, Qingbo; Lang, Jinghe (Frontiers in Medicine, 2021)
Background: Abdominal aggressive fibromatosis (AF) can be confounded with abdominal wall endomentriosis (AWE) because they share considerable similarity. Because of the different patient prognoses and treatment strategies available, accurate pre-operative diagnosis is important. Case Presentation: We here report two cases of abdominal masses presenting as periodic changes in tumor sizes, which occurred in correlation with the menstrual cycle. The clinical findings were highly suggestive of AWE. However, the final pathological findings revealed AF. The estrogen receptor and progesterone receptor expressions were negative in the two cases. The differences between the two diseases have been discussed in detail. Conclusion: A diagnosis of AWE should be scrutinized closely if the patient does not complain of cyclic pain. Fine-needle aspiration cytology is a suitable tool for preoperative evaluation.